Pharmacoeconomic evaluation of pramipexole extended release monotherapy in early Parkinson's disease - D. Yu. Belousov; E. V. Afanasyeva (Izdatelstvo OKI, 2018)
Objective. Health economic expertise of pramipexole extended release monotherapy at early stages of Parkinson's disease. Methods. An economic model was developed based on clinical studies to derive comparative information on the effectiveness, utility and direct medical costs of antiparkinsonian treatment strategies over a year period. Cost-effectiveness, cost-utility and budget impact of comparative therapies were assessed. Results. Mirapex® extended release (ER) has the lowest cost-effectiveness ratio (31 499 rub. per a patient a year responded to antiparkinsonian therapy) and the lowest cost-utility ratio (2 562 rub. for decrease of degree of abnormalities of daily activities and motive abnormalities per a point of UPDRS scale). Budget impact analysis demonstrated that pramipexole ER monotherapy resulted in cost saving of 6 499 rub. (20 %) compared to Pronoran®, 26 918 rub. (51%) compared to Requip Modutab® and 24 966 rub. (49%) compared to Azilect® per a year of therapy. Mirapex® ER was the dominant strategy demonstrating higher effectiveness at lower costs in Parkinson's disease treatment.